First record of Cnemidochroma phyllopus (Coleoptera: Cerambycidae) in the province of Corrientes, Argentina and potential distribution in the southern part of South America - Valle, Néstor G.; Ibarra-Polesel, Mario G.; Cherman, Mariana Alejandra; Monné, Marcela L.; Damborsky, Miryam P. (Zootaxa, 2021)
Cnemidochroma Schmidt, 1924, a small genus of the tribe Callichromatini endemic in South America, comprises six species of which the only one recorded in Paraguay, Uruguay, Argentina and Brazil is C. phyllopus (Guérin-Méneville, 1844). The aim of this study was to estimate potential suitable areas for C. phyllopus to provide further knowledge on its current distribution. A dataset of 43 records was compiled and species distribution modelling was employed linking these occurrences with bioclimatic variables. Results indicate higher suitability conditions along the Atlantic coast of Brazil, reaching north Uruguay and extending inland to Paraguay and northern parts of Argentina. In addition, we report a new distributional record from Corrientes, Argentina.